Розвиток ідей А.М. Гродзінського про фітодизайн - Snezhko, V.V.; Kharytonova, I.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The results of many years researches on phytodesign are given in this paper. The modern approaches to phytodesign need as careful sampling of tropical and subtropical plants according to their ornamental character, as considering plant resistance to extreme conditions of cultivation. The data on tropical and subtropical plants reaction on microclimate in interiors of miscellaneous functionality are shown.